FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK KENDARAAN BERMOTOR (Universitas Gresik, 2023)
The implementation of this research aims to analyze the level of taxpayer compliance in paying PKB which is influenced by the application of E-SAMSAT and tax sanctions. In addition, this research will also make observations about what aspects can trigger the level of compliance in paying taxes. Then the selection of sample data applies a random sampling method of 100 taxpayers in the Mojokerto area which is the research population. While the data collection method applies a questionnaire whose assessment technique uses a Likert scale with four assessment categories. So that the research data obtained is of the primary data type. Then the research instrument testing method applies the reliability test with the Cronbach-alpha technique and the validity test with the person correlation technique and the multiple linear regression test to analyze the research data. Based on testing and analysis, it is obtained that the level of taxpayer compliance is significantly influenced by E-SAMSAT, tax sanctions, and knowledge.